2015
DOI: 10.1098/rspb.2014.2032
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity at birth predicted infant survival and women's fertility in historical Norway

Abstract: Ultraviolet radiation (UVR) can suppress essential molecular and cellular mechanisms during early development in living organisms and variations in solar activity during early development may thus influence their health and reproduction. Although the ultimate consequences of UVR on aquatic organisms in early life are well known, similar studies on terrestrial vertebrates, including humans, have remained limited. Using data on temporal variation in sunspot numbers and individual-based demographic data (N ¼ 8662… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…A recent large-scale Norwegian study indicates that solar activity at birth predicts infant survival and women's fertility. 71 The authors relate this phenomenon to possible UV-R-related effects on vitamin D and folate and discuss the possible role of vitamin-related gene variants. This study builds on the work of Lucock and colleagues [22][23][24] and is supported by similar earlier large studies that indicate that month of birth 72 and the solar cycle 73 actually influence longevity, with Marzullo and Fraser 58 reporting that the human embryo responds to both photoperiod and oxidant stress and suggest that later life disease correlates could be a consequence of this.…”
Section: Vitamin D Health Correlates Including a Perspective On Seasomentioning
confidence: 99%
“…A recent large-scale Norwegian study indicates that solar activity at birth predicts infant survival and women's fertility. 71 The authors relate this phenomenon to possible UV-R-related effects on vitamin D and folate and discuss the possible role of vitamin-related gene variants. This study builds on the work of Lucock and colleagues [22][23][24] and is supported by similar earlier large studies that indicate that month of birth 72 and the solar cycle 73 actually influence longevity, with Marzullo and Fraser 58 reporting that the human embryo responds to both photoperiod and oxidant stress and suggest that later life disease correlates could be a consequence of this.…”
Section: Vitamin D Health Correlates Including a Perspective On Seasomentioning
confidence: 99%
“…Also, it is shown that X-rays cause apoptosis in the sexual cells ( 32 ). As well as, it has been shown that UV ray prevents the molecular and cellular mechanisms of sexual growth in the early stages of life ( 33 ). Researchers have shown that high levels of ultraviolet rays have a delayed effect on the retention and production of reproductive cells ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barker's "developmental" model for the origins of a wide range of chronic diseases links their cause to variations in fetoplacental development, thought to lead to variations in the supply of nutrients to the baby that permanently alter gene expression [84]. In a study of demographic data in historical Norway, the lifespans of individuals born during a span of solar maximum were found to be 5.2 years shorter than those born during a span of solar minimum, while fertility and lifetime reproductive success were reduced among low-status women [85]. Anthropometric measures at birth have also been found to follow about 10.5-and about 21-year cycles [57], perhaps in response to cycles in agriculture, following cycles in weather and climate.…”
Section: Possible Underlying Mechanismsmentioning
confidence: 99%